2020
DOI: 10.1088/1757-899x/814/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Gas sensing properties of BaxSr1-xTiO3 (with x=0.5 and x=0.7) thin films grown using Pulse Laser Deposition

Abstract: Thin films of Barium Strontium Titanate (BST) have been fabricated using Pulse Laser Deposition (PLD) technique. Two stoichiometries of BaxSr1-xTiO3 with x=0.5 and x=0.7 are deposited on well cleaned quarts substrates in high vacuum chamber with oxygen pressure of 0.13mbar at 700˚C. XRD pattern shows perovskite structure of the films. Energy Dispersive X-ray (EDX) is used to determine the element concentration of both the films. Transmittance spectra of UV characterization shows decrement in transparency of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…103 Shastri et al fabricated Ba x Sr (1Àx) TiO 3 (x = 0.5 and 0.7)/PVATFs, using the PLD method to be used as an H 2 S gas sensor. 103 Tommalieh et al developed PVA/Chitosan thin films doped with various concentrations of gold NPs through the PLD method. 104 Menazea et al also fabricated carboxymethyl cellulose (CMC)/PVA doped with gold NPs using the PLD technique.…”
Section: Pulsed Laser Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…103 Shastri et al fabricated Ba x Sr (1Àx) TiO 3 (x = 0.5 and 0.7)/PVATFs, using the PLD method to be used as an H 2 S gas sensor. 103 Tommalieh et al developed PVA/Chitosan thin films doped with various concentrations of gold NPs through the PLD method. 104 Menazea et al also fabricated carboxymethyl cellulose (CMC)/PVA doped with gold NPs using the PLD technique.…”
Section: Pulsed Laser Depositionmentioning
confidence: 99%
“…Pulsed laser deposition (PLD) is a physical vapor deposition technique that uses a high‐power density laser beam under vacuum conditions to vaporize the target material to form a plasma plume, which is to be deposited on a substrate as a thin film 102 . A schematic representation of this technique is given in Figure 10 103 . Shastri et al fabricated Ba x Sr (1− x ) TiO 3 ( x = 0.5 and 0.7)/PVATFs, using the PLD method to be used as an H 2 S gas sensor 103 .…”
Section: Various Applications Of the Pvatfsmentioning
confidence: 99%
“…The reason for the rapid response of the sensor could then be an increase in the concentration of the cationic void near the interface, induced by the space charge. Cationic voids are the cause of high electron depletion [70]. In the same year, Hu et al presented a low-temperature nano-structured SrTiO 3 thick-film oxygen sensor obtained by utilization of the high-energy ball milling technique in conjunction with the screen printing technique.…”
Section: Srtio 3 For Gas-sensing Applicationsmentioning
confidence: 99%
“…The authors reported that at 250 • C, 50% RH and 10 ppm of H 2 S concentration, Cu 5% BST showed good stability in electrical resistance: R air = 4.25•10 10 ± 20% Ω, R H2S = 5.61•10 8 ± 13.7% Ω (response S = R air /R H2S , S = 75.76). Recently, results on the gas-sensing properties of BST: Ba 0.5 Sr 0.5 TiO 3 (BST0.5) and Ba 0.7 Sr 0.3 TiO 3 (BST0.7) thin films under H 2 S exposure (800 ppm) in the temperature range of 50-380 • C were presented in [70]. The gas sensors based on both BSTs, i.e., 0.5/0.5 and 0.7/0.3, reached the maximum response (57.57% and 41.61% for BST 0.5 and BST 0.7 , respectively) at 330 • C. BST-based nanomaterials have also found application in the detection of NH 3 gas [101][102][103].…”
Section: Basrtio 3 For Gas-sensing Applicationsmentioning
confidence: 99%
See 1 more Smart Citation